AIAA SPACE 2008 Conference &Amp; Exposition 2008
DOI: 10.2514/6.2008-7711
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Selection for a Space Power Grid

Abstract: This paper continues work on an evolutionary, revenue-generating approach to Space Solar Power. In previous work, a 3-stage, self-sustaining program was proposed, that enables growth to full Space Solar power in 20 to 30 years. The approach is to first use a constellation of spacecraft in sun-synchronous orbits as a microwave power grid connecting renewable energy plants situated around the world. This step generates revenue primarily from the large temporal and geographic variations in cost and supply of elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…ESTABLISHING SYSTEM SIZE AND POWER LEVEL In Ref. [17] we explored the minimum size of the Phase 1 system, required to make it self-sustaining regardless of the implementation of Phases 2 and 3. Such a system would require the motivations that drive Space agencies worldwide, and hence must have SSP as an ultimate goal.…”
Section: Economics Of the Space Power Gridmentioning
confidence: 99%
“…ESTABLISHING SYSTEM SIZE AND POWER LEVEL In Ref. [17] we explored the minimum size of the Phase 1 system, required to make it self-sustaining regardless of the implementation of Phases 2 and 3. Such a system would require the motivations that drive Space agencies worldwide, and hence must have SSP as an ultimate goal.…”
Section: Economics Of the Space Power Gridmentioning
confidence: 99%
“…Such a system involving global power exchange obviously requires international collaboration on a global scale. Komerath et al (2007) proposes a global public-private Consortium, partially based on the model for the European Space Agency, where member nations and private corporations collaborate to reduce risk, make low-interest funding available, and organize the construction of major Space infrastructure. This set up is also shown to be open a path towards resolving some of the most vexing obstacles in space resource utilization, arising from current Space Law.…”
Section: Typical Halo Orbitmentioning
confidence: 99%
“…The cost and revenue aspects of the system were estimated at a zeroth-order level, and the results suggested that the system could be developed to the full SSP stage within 30 years at a reasonable level of public investment if the conversion efficiency became acceptable. In a recent paper at the AIAA Space 2008 conference (Komerath, 2008), we compared the economics of approaches using different frequencies and choices of orbits. It is seen that approaches using frequencies lower than 100 GHz are not viable, confirming the pessimism of those who have been struggling with traditional SSP concept for decades.…”
Section: Introductionmentioning
confidence: 99%
“…Possible efficiencies in this regime 4. Choices of orbits Establishing System Size and Power Level Komerath (2008) explored the minimum size of the Phase 1 system, required to make it self-sustaining regardless of the implementation of Phases 2 and 3. This is of course a steep requirement, as we have no evidence that the nations of the world would embark on a space-based grid solution to the issues of developing renewable energy plants.…”
Section: Introductionmentioning
confidence: 99%